Naturally acquired antibody response to Plasmodium falciparum and Plasmodium vivax among indigenous Orang Asli communities in Peninsular Malaysia - Rahim, Mohd Amirul Fitri A.; Munajat, Mohd Bakhtiar; Dian, Nor Diyana; Seri Rakna, Mohd Ikhwan Mukmin; Wahid, Wathiqah; Ghazali, Nuraffini; Hassan, Noor Wanie; Abdul Manap, Siti Nor Azreen; Kasri, Muhd Rafiq Mohd; Mohamed, Ahmad Imran; Osman, Emelia; Chuangchaiya, Sriwipa; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Malaria remains a public health problem in many parts of the world. In Malaysia, the significant progress towards the national elimination programme and effective disease notification on malaria has resulted in zero indigenous human malaria cases since 2018. However, the country still needs to determine the extent of malaria exposure and transmission patterns, particularly in high-risk populations. In this study, a serological method was used to measure transmission levels of Plasmodium falciparum and Plasmodium vivax among indigenous Orang Asli communities in Kelantan, Peninsular Malaysia. A community-based cross-sectional survey was conducted in three Orang Asli communities (i.e., Pos Bihai, Pos Gob, and Pos Kuala Betis) in Kelantan from June to July 2019. Antibody responses to malaria were assessed by enzyme-linked immunosorbent assay (ELISA) using two P. falciparum (PfAMA-1 and PfMSP-119) and two P. vivax (PvAMA-1 and PvMSP-119) antigens. Age-adjusted antibody responses were analysed using a reversible catalytic model to calculate seroconversion rates (SCRs). Multiple logistic regression was used to investigate factors associated with malaria exposure. The overall malaria seroprevalence was 38.8% for PfAMA-1, 36.4% for PfMSP-119, 2.2% for PvAMA-1 and 9.3% for PvMSP-119. Between study areas, the proportion of seropositivity for any P. falciparum and P. vivax antigens were significantly highest in Pos Kuala Betis with 34.7% (P < 0.001) and 13.6% (P < 0.001), respectively. For all parasite antigens except for PvAMA-1, the proportion of seropositive individuals significantly increased with age (all P < 0.001). Based on the SCR, there was a higher level of P. falciparum transmission than P. vivax in the study area. Multivariate regression analyses showed that living in Pos Kuala Betis was associated with both P. falciparum (adjusted odds ratio [aOR] 5.6, P < 0.001) and P. vivax (aOR 2.1, P < 0.001) seropositivities. Significant associations were also found between age and seropositivity to P. falciparum and P. vivax antigens. Analysis of community-based serological data helps describe the level of transmission, heterogeneity and factors associated with malaria exposure among indigenous communities in Peninsular Malaysia. This approach could be an important adjunct tool for malaria monitoring and surveillance in low malaria transmission settings in the country.